1981
DOI: 10.1149/1.2127636
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation, Impurity Diffusion, and Defect Growth in Silicon—An Overview

Abstract: As a result of a large body of literature on oxidation, impurity diffusion, and defect growth in silicon, a consistent picture has emerged of oxidationenhanced diffusion (OED) and oxidation-induced stacking fault growth (OISF). It is believed that silicon self-interstitials can be generated at an oxidizing Si/SiO2 interface as a result of an incomplete half-cell reaction involving silicon and oxygen. Those interstitials that do not participate in surface regrowth participate in raising the steady-state concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
2
2

Year Published

1981
1981
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(20 citation statements)
references
References 39 publications
0
16
2
2
Order By: Relevance
“…The observed power exponent, about 0.2, is much smaller than that expected in previous studies (11)(12)(13)(14)(15)(16). The observed power exponent, about 0.2, is much smaller than that expected in previous studies (11)(12)(13)(14)(15)(16).…”
Section: Resultscontrasting
confidence: 73%
See 2 more Smart Citations
“…The observed power exponent, about 0.2, is much smaller than that expected in previous studies (11)(12)(13)(14)(15)(16). The observed power exponent, about 0.2, is much smaller than that expected in previous studies (11)(12)(13)(14)(15)(16).…”
Section: Resultscontrasting
confidence: 73%
“…Previous self-interstitial generation models (11)(12)(13)(14)(15) paid much attention to the interstitial flux into bulk silicon. In a previous paper (34), however, we reported that an OSF growth experiment and simulation had established that the interstitial flux into the substrate is too small to perturb the concentration at the interface.…”
Section: N E W Physical M O D E L --S I N C E the Effective Diffusivimentioning
confidence: 99%
See 1 more Smart Citation
“…[25][26][27] Although there are some differences in the approach taken by different authors, the most accepted one is that retrogrowth of OISFs occurs at high temperatures (1240°C) or long oxidation times (> 10 h) because the self-interstitial supersaturation (S I ) is suppressed by point defect recombination. [25][26][27] Although there are some differences in the approach taken by different authors, the most accepted one is that retrogrowth of OISFs occurs at high temperatures (1240°C) or long oxidation times (> 10 h) because the self-interstitial supersaturation (S I ) is suppressed by point defect recombination.…”
Section: Growth and Retrogrowth Of Oisf In Simoxmentioning
confidence: 99%
“…The glass transition temper-Key words: positive electron resist, methacrylonitrile, trichloroethyl, methacrylate, copolymer. ature (Tg) of PMCN is 120~ (2), which is higher than the Tg of PMMA, which is I00~ Further, it has been shown that PMCN is one of the few aliphatic vinyl polymers that has high plasma etch resistance (3).…”
Section: Studies Of Methacrylonitrile and Trichloroethylmentioning
confidence: 99%